THE USE OF SONGS TO IMPROVE STUDENTS’ LISTENING COMPREHENSION ABILITY - Lestary, Ni Luh Gede Windy (Institut Hindu Dharma Negeri Denpasar, 2019)
The aim of this journal is to find out the utilization of songs as the technique of teaching listening. Listening is part of four Basic English language skills. It seems like the other skills such as writing, reading, and speaking. These basic skills are divided into receptive skill-listening and reading- and productive skill, speaking and writing. Music and songs are crucial parts of growing and learning. There are many advantages to using songs in the classroom. There are positive and negative views on the utilization of songs in foreign language teaching. Using songs in the learning process especially in the listening lesson it makes the students can improve their listening skill as one of their meaningful strategies to overcome their problem in listening skill. English song can make the students become active in the class, they are interesting, and so they can do a listening task well. However, utilizing songs in the listening process has the challenges, such as; pop songs are not scientific, and inefficient sound systems in schools may cause problems while listening to songs, etc.